METHODOLOGICAL FOUNDATIONS OF TEACHING THE RUSSIAN LANGUAGE IN MODERN EDUCATION - Ulashova Nilufar Dadaboyevna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article examines modern strategies and instructional techniques used in teaching the Russian language in contemporary educational contexts. Ongoing changes in pedagogical theory and practice have led to a shift from traditional, form- oriented instruction toward approaches that emphasize communicative competence, learner autonomy, and meaningful language use. The study analyzes key methodological trends, including communicative teaching, learner-centered instruction, task-based and project-based learning, as well as interactive and reflective practices. Special attention is given to the role of instructional methods in enhancing students’ cognitive engagement, motivation, and practical language skills. The analysis shows that the systematic integration of diverse teaching strategies and techniques creates favorable conditions for effective language acquisition and supports the development of functional communicative competence. The findings highlight that successful Russian language teaching depends on the purposeful combination of modern pedagogical approaches adapted to learners’ needs and educational objectives. The results of the study may be useful for language teachers, curriculum designers, and researchers interested in improving the quality of Russian language education.